Quantification of cell-free DNA for evaluating genotoxic damage from occupational exposure to car paints (2016)
Background: For several years, cell-free DNA has been emerging as an important biomarker for non-invasive diagnostic in a wide range of clinical conditions and diseases. The limited information available on the genotoxic effects associated with occupational exposure to car paints, as well as the fact that up-to-date there are not reports about cell-free DNA measurements for assessing this condition, led us to evaluate the DNA damage caused by the occupational exposure to organic solvents contained in car paints, through the quantification of the cell-free DNA and the comet assay, in a sample of 33 individuals taken from 10 automobile paint shops located in Bogota DC, Colombia. Results: By applying the two methods, cell-free DNA and comet assay, we found a significant increase in the extent of DNA damage in the exposed individuals compared with the non-exposed ones within the control group. Conclusions: Our findings provide useful information about the cell-free DNA levels in this type of exposure and can be considered as a support tool that contributes to the diagnosis of genotoxic damage in individuals occupationally exposed to car paints. © 2016 The Author(s).